MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI MTsN 4 PIDIE - Nasri Diana; Bukhari; Nazatur Rahmi (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan, 2023)
The purpose of this study was to determine whether the use of audio-visual media could improve student learning outcomes at MTsN 4 Pidie. The study employed a descriptive qualitative approach, specifically a case study method. The research instrument used was a closed-ended questionnaire consisting of 15 multiple-choice questions. The study population comprised 276 Grade VIII students (121 boys and 155 girls) and two Islamic Cultural History (SKI) teachers at MTsN 4 Pidie. The sample consisted of the two SKI teachers and 55 Grade VIII students (representing 20% ​​of the total student body in that grade): 28 students from class VIII-1 (11 male, 17 female) and 27 students from class VIII-2 (10 male, 17 female). The results showed that 39 students (70.9%) provided responses indicating a satisfactory outcome. Thus, it can be concluded that the application of audio-visual media influences student learning outcomes at MTsN 4 Pidie.